Fear of Missing Out (FOMO): Exploring Its Relationship with Self-Control and Self-Regulation in College Students - Amelisastri, Windy; Yandri, Hengki; Kholidin, Farid Imam (Buletin Konseling Inovatif, 2025)
This study investigates the potential influence of self-control and self-regulation on Fear of Missing Out (FoMO) among students. FoMO is characterized by an apprehension of being excluded from significant experiences or opportunities. Individuals with low self-control may struggle to prioritize positive behaviors, potentially leading to heightened FoMO. Similarly, a lack of self-regulation, the ability to manage thoughts and guide actions towards goals, might exacerbate FoMO. The current research employs a quantitative, descriptive correlational design. The study population comprised 2,245 students from the Faculty of Tarbiyah and Teacher Training at Institut Agama Islam Negeri Kerinci. A sample of 304 participants, representing 10 departments, was selected. Data collection utilized three validated scales: the Self-Control Scale, the Self-Regulation Questionnaire, and the Fear of Missing Out Scale. The hypothesis proposing a significant negative association between self-control/self-regulation and FoMO was supported (p < 0.05). This suggests that both self-control and self-regulation have a combined effect on FoMO. In simpler terms, individuals with greater self-control and self-regulation may experience lower levels of FoMO. Future research could explore specific factors contributing to FoMO development. Additionally, expanding the sample size might enhance the generalizability of findings.